Design Analysis of Beams, Circular Plates and Cylindrical Tanks on Elastic Foundation: With IBM-compatible Software - MELERSKI, Edmund S (Taylor & Francis, 2006)
Design Analysis of Beams, Circular Plates and Cylindrical Tanks on Elastic Foundation